Anaplasma phagocytophilum increases the levels of histone modifying enzymes to inhibit cell apoptosis and facilitate pathogen infection in the tick vector Ixodes scapularis - Cabezas-Cruz, Alejandro; Alberdi, Pilar; Ayllón, Nieves; Valdés, James J; Pierce, Raymond; Villar, Margarita; de la Fuente, José (Epigenetics, 2016)
Epigenetic mechanisms have not been characterized in ticks despite their importance as vectors of human and animal diseases worldwide. The objective of this study was to characterize the histones and histone modifying enzymes (HMEs) of the tick vector Ixodes scapularis and their role during Anaplasma phagocytophilum infection. We first identified 5 histones and 34 HMEs in I. scapularis in comparison with similar proteins in model organisms. Then, we used transcriptomic and proteomic data to analyze the mRNA and protein levels of I. scapularis histones and HMEs in response to A. phagocytophilum infection of tick tissues and cultured cells. Finally, selected HMEs were functionally characterized by pharmacological studies in cultured tick cells. The results suggest that A. phagocytophilum manipulates tick cell epigenetics to increase I. scapularis p300/CBP, histone deacetylase, and Sirtuin levels, resulting in an inhibition of cell apoptosis that in turn facilitates pathogen infection and multiplication. These results also suggest that a compensatory mechanism might exist by which A. phagocytophilum manipulates tick HMEs to regulate transcription and apoptosis in a tissue-specific manner to facilitate infection, but preserving tick fitness to guarantee survival of both pathogens and ticks. Our study also indicates that the pathogen manipulates arthropod and vertebrate cell epigenetics in similar ways to inhibit the host response to infection. Epigenetic regulation of tick biological processes is an essential element of the infection by A. phagocytophilum and the study of the mechanisms and principal actors involved is likely to provide clues for the development of anti-tick drugs and vaccines.
Keywords: Anaplasma; Ixodes; transkripční faktory p300-CBP; pathogen; Epigenesis, Genetic; Humans; messenger RNA; histony; Host-Pathogen Interactions; Insect Vectors; interakce hostitele a patogenu; klíště; histonový kód; lidé; zvířata; histone; apoptóza; buněčné linie; epigenetics; epigeneze genetická; tick; RNA, Messenger; Cell Line; hmyz - vektory; Histone Code; Histones; transkriptom; Transcriptome; p300-CBP Transcription Factors; Animals; histone modifying enzyme; Apoptosis; Anaplasma phagocytophilum